Les dérivés nominaux de noms propres en tant qu’insultes dans le discours médiatique polonais - Kochanowska, Anna (Studia Romanica Posnaniensia, 2017)
The aim of the article is to study simple nominal derivatives created from the acronym of the Polish political party Prawo i Sprawiedliwość (Law and Justice). In some forms of media discourse, these derivatives function as insults and are among many instruments of hate speech.